Posttranslational oxidative modification of (R)‐2‐(2, 4‐dichlorophenoxy)propionate/α‐ketoglutarate‐dependent dioxygenases (RdpA) leads to improved degradation of 2, 4‐dichlorophenoxyacetate (2, 4‐D). Issue 3 (24th January 2013) - Leibeling, Sabine; Maeß, Marten B.; Centler, Florian; Kleinsteuber, Sabine; von Bergen, Martin; Thullner, Martin; Harms, Hauke; Müller, Roland H.
<x xml:space="preserve">Abstract</x> Microbial activities and the versatility gained through adaptation to xenobiotic compounds are the main biological forces to counteract environmental pollution. The current results present a new adaptive mechanism that is mediated through posttranslational modifications. Strains of Delftia acidovorans incapable of growing autochthonously on 2, 4‐dichlorophenoxyacetate (2, 4‐D) were cultivated in a chemostat on 2, 4‐D in the presence of (R)‐2‐(2, 4‐dichlorophenoxy)propionate. Long‐term cultivation led to enhanced 2, 4‐D degradation, as demonstrated by improved values of the Michaelis–Menten constant Km for 2, 4‐D and the catalytic efficiency kcat/Km of the initial degradative key enzyme (R)‐2‐(2, 4‐dichlorophenoxy)propionate/α‐ketoglutarate‐dependent dioxygenases (RdpA). Analyses of the rdpA gene did not reveal any mutations, indicating a nongenetic mechanism of adaptation. 2‐DE of enzyme preparations, however, showed a series of RdpA forms varying in their pI. During adaptation increased numbers of RdpA variants were observed. Subsequent immunoassays of the RdpA variants showed a specific reaction with 2, 4‐dinitrophenylhydrazine (DNPH), characteristic of carbonylation modifications. Together these results indicate that posttranslational carbonylation modified the substrate specificity of RdpA. A model was implemented explaining the segregation of clones with improved degradative activity within the chemostat. The process described is capable of quickly responding to environmental conditions by reversibly adapting the degradative potential to various phenoxyalkanoate herbicides.